Pemberdayaan dan Diversifikasi Produk Olahan Daun Kelor pada Ibu PKK Kelapa Sawit dalam Upaya Pencegahan Stunting: Empowerment and Diversification of Moringa Leaf Processed Products for Kelapa Sawit PKK Mothers in an Effort to Prevent Stunting - Wati, Helmina; Saputri, Revita; Abdurrahman, Abdurrahman; Widyanto, Rinto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Stunting is defined as a failure to achieve optimal growth, as measured by height for age. Moringa leaves have been demonstrated to improve the nutritional status of toddlers based on body mass index according to age. In Banjarbaru, Sungai Besar village, palm oil is found to contain a significant amount of moringa leaves. This community service activity aims to empower palm oil PKK mothers and diversify moringa leaf processed products. The community service method involved counseling activities related to the benefits of moringa leaves and assistance in moringa leaf diversification. The results of the service included moringa leaf, areca nuts, and healthy snacks with a taste, shape, and color that the community liked. It can be concluded that there was an increase in the skills of PKK palm oil mothers in making processed moringa leaf products.